Integrating Underutilized Black Volunteers in 4-H Youth Development Programs - Maurice Smith; Shannon Wiley ([TEST] Journal of Extension, 2021)
4-H Youth Development prides itself on providing essential resources to reach underserved minority populations. 4-H provides programming and professional development for volunteers to include diverse hands-on training, and cultural competency workshops. This article provides best practices for the inclusion of African American volunteers in 4-H programming efforts that could help extension educators better understand the need to include minority volunteer roles and responsibilities. These strategies include strengthening diverse volunteer make-up, increasing participation and trust among African American youth, and engaging volunteers working in educational organizations that could provide real world experiences for youth.
Keywords: African American; 4-H Youth Development; volunteers; Underserved Communities